Skeletal Stability of Two-Jaw Surgery Without Bone Grafting in Patients With Cleft Lip and Palate. Issue 2 (20th March 2022) - Jang, Hun; Park, Jin-Young; Choi, Na-Rae; Hwang, Dae-Seok
Abstract : Purpose: The purpose of this study was to evaluate the postoperative skeletal stability of orthognathic surgery performed without a bone graft in cleft lip and palate patients. Patients and Methods: Nineteen cleft lip and palate patients that underwent orthognathic surgery from July 2008 to August 2019 at the Department of Oral and Maxillofacial Surgery of Pusan National University Dental Hospital were selected. None of these patients underwent bone grafting during orthognathic surgery. Lateral cephalograms were taken 1 month before surgery (T0), immediately after surgery (T1), and 6 months after surgery (T2). Lateral cephalograms were analyzed using the V-Ceph program. The analysis was performed using SPSS for Windows version 26.0. The analysis was conducted by repeated-measures analysis of variance. Results: A total of 19 patients were included in this retrospective study (9 males/10 females of overall mean age 22 ± 4.89 years). Mean maxillary depth values at the 3-time points were 85.37° ± 2.62° (T0), 90.13° ± 2.77° (T1), and 89.29° ± 2.91° (T2). Mean McNamara–N Perpend values were −5.52 ± 3.19 mm (T0), 0.09 ± 3.10 mm (T1), and −0.83 ± 3.14 mm (T2). Mean sella nasion point A (SNA) values were 75.42° ± 2.98° (T0), 79.19° ± 2.94° (T1), and 78.45° ± 2.84° (T2). Mean relapse rates were maxillary depth 20.15%, McNamara–N Perpend 17.95%, and SNA 18.74%. Mean horizontal advancement was 5.61 ± 2.32 mm based on McNamara vertical to A point, mean horizontal relapse was -0.92 ± 0.56 mm, and the mean horizontal relapse rate was 17.95%. Conclusions: Favorable skeletal stability can be obtained without bone graft when the amount of maxillary advancement is less than 6 mm in cleft patients.